1988
DOI: 10.3109/00016488809106423
|View full text |Cite
|
Sign up to set email alerts
|

Experimental paralysis of tensor veli palatini muscle

Abstract: In an effort to study the effects of experimental paralysis of tensor veli palatini (TVP) muscle on Eustachian tube (ET) function and middle-ear (ME) status, botulinum toxin A (Oculinum) was injected into the TVP muscles of 8 Rhesus monkeys. Tubal function was tested longitudinally in 2 animals with tympanostomy tubes using the forced-response test, while in the remaining 6 animals; ME condition was documented daily using tympanometry. The postinjection tubal function was characterized by abolished active musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 16 publications
2
67
1
Order By: Relevance
“…The fall of the fluid level in this tube can serve as a measure of the rate of absorption of water from the middle ear cavity. Since it has been shown that paralysis of the tensor veli palatine muscle leads to obstruction of the eustachian tube [Casselbrant et al, 1988], all of the animals were paralyzed (and artificially ventilated) so that the eustachian tube pumping mechanism could not be activated and accordingly the eustachian tube itself was not patent, preventing clearance by the beating cilia of the mucociliary mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…The fall of the fluid level in this tube can serve as a measure of the rate of absorption of water from the middle ear cavity. Since it has been shown that paralysis of the tensor veli palatine muscle leads to obstruction of the eustachian tube [Casselbrant et al, 1988], all of the animals were paralyzed (and artificially ventilated) so that the eustachian tube pumping mechanism could not be activated and accordingly the eustachian tube itself was not patent, preventing clearance by the beating cilia of the mucociliary mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…In the atypical swallowers the perioral muscles show a greater activity than masticatory muscles when compared with control subjects, as demonstrated by electromyographic studies [19]. In particular, past experiences postulated that hypertonia of the internal perioral muscle caused by swallowing dysfunction can produce a reflex hypertonia of the tensor tympani muscles and a relative hypotonia of the mTVP; this may result in an ineffective opening of the ET and poor ventilation of the middle ear cavity [20].…”
Section: Discussionmentioning
confidence: 97%
“…Because there is a risk of such side effects (as seen in animal studies 10,11 ), we assume that they are dependent on the dose and on the site of application. In our case, a BT (type A) dose of 2.5 U into the salpingopharyngeal fold was optimal.…”
Section: Endoscopy (Posterior Rhinoscopy)mentioning
confidence: 99%
“…10,11 The BT-induced paralysis of the tensor veli palatini muscle was successful in a human case of palatal tremor. 18,21 Botulinum toxin interferes with presynaptic acetylcholine release at the neuromuscular junction and is established as a standard therapy for a wide spectrum of diseases.…”
Section: Introductionmentioning
confidence: 98%